2018
DOI: 10.1007/s12272-018-1017-3
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic dopamine receptor antagonists, cancer, and cancer stem cells

Abstract: Cancer is one of the deadliest diseases in the world. Despite extensive studies, treating metastatic cancers remains challenging. Years of research have linked a rare set of cells known as cancer stem cells (CSCs) to drug resistance, leading to the suggestion that eradication of CSCs might be an effective therapeutic strategy. However, few drug candidates are active against CSCs. New drug discovery is often a lengthy process. Drug screening has been advantageous in identifying drug candidates. Current understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 270 publications
0
43
0
Order By: Relevance
“…Interestingly, previous studies have already shown antiproliferative and migrastatic effects of pimozide in pancreatic cancer cells with high expression levels of DRD2, MDA‐MB‐231 breast cancer cells, and A549 lung cancer cells . Consequently, many antipsychotic dopamine receptor antagonists have recently been tested in a variety of cancer cells, and these drugs inhibit the growth of cancer cells through the modulation of different targets, such as DRD2, STAT, and AKT .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have already shown antiproliferative and migrastatic effects of pimozide in pancreatic cancer cells with high expression levels of DRD2, MDA‐MB‐231 breast cancer cells, and A549 lung cancer cells . Consequently, many antipsychotic dopamine receptor antagonists have recently been tested in a variety of cancer cells, and these drugs inhibit the growth of cancer cells through the modulation of different targets, such as DRD2, STAT, and AKT .…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports indicating elevated DRD2 expression in cancer cells compared to normal cells in several cancer types, and DRD2 overexpression correlates with an advanced stage and stemness of cancer and a poor prognosis of patients 7 , 9 , 24 . Moreover, antagonizing DRD2 signaling either by DRD2 antagonists, such as thioridazine and trifluoperazine, or genetic depletion show the proapoptotic, antimetastatic, antiangiogenic, and anticancer stem cell properties in several tumor types 7 , 10 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports indicating elevated DRD2 expression in cancer cells compared to normal cells in several cancer types, and DRD2 overexpression correlates with an advanced stage and stemness of cancer and a poor prognosis of patients 7 , 9 , 24 . Moreover, antagonizing DRD2 signaling either by DRD2 antagonists, such as thioridazine and trifluoperazine, or genetic depletion show the proapoptotic, antimetastatic, antiangiogenic, and anticancer stem cell properties in several tumor types 7 , 10 , 25 . At present, DRD2 genetic variants have been reported to affect the expression and function of DRD2 and to be correlated with the susceptibility and clinicopathologic development of cancers such as colon and lung cancers, and pituitary adenomas 17 , 18 , 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations